ANALISIS SIKAP KERJA KARYAWAN PERBANKAN SYARIAH BERDASARKAN KARAKTERISTIK BIOGRAFIS - Siswanto Muhammad, Sulhan (El-QUDWAH, 2011)
The purpose  of  this  study  is  to  compare  job  satisfaction  and  organizational commitment  of  employee’s  Islamic  banking  based  on  biographical  characteristics. Biographical characteristics are consists of age, gender, marital status, and education. Total  sample  in  the  research  are  125  respondents.  Data  analysis  is  executed  by independent samples t-test and Analysis of Varians (Anova) with SPSS 16 version. Based on the research indicate that employee job satisfaction is quitely different between men and women.  Organizational commitment based on gender is quietly different too. Job satisfaction and organizational commitment of men are higher than women. Managerial  implications  of  human  resource  management  requires  to  enhance  an organizational commitment and job satisfaction of Islamic banking women employeesKeywords: Satisfaction, Organizational Commitment, Islamic Bank